1985
DOI: 10.1177/073346488500400206
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease: Caregivers' Perceptions of Burden

Abstract: The purpose of this study was to examine factors contributing to the burden of primary caregivers of Alzheimer's Disease patients. Burden was measured by the Burden Interview while the patient's level of functioning was rated by caregivers on the Symptom Questionnaire and the Dementia Rating Scale. In addition, the relationship between burden and a number of other relevant variables including stress responses, help orientation, social support, and predisease caregiver-patient relationship was assessed. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…A relationship between disability and stress has at times been confirmed (Deimling & Bass, 1986;Schulz, Tompkins, Wood, & Decker, 1987;Stoller & Pugliesi, 1989), but more commonly not (George & Gwyther, 1986;Haley, Levine, Brown, & Bartolucci, 1987;Kinney & Stephens, 1989;Moritz, Kasl, & Berkman, 1989;Morris et al, 1988;Pagel et al, 1985). Similarly, a positive relationship between caregiver and care receiver has been seen as beneficial (Gilleard, Gilleard, Gledhill, & Whittick, 1984;Horowitz, 1985;Morris et al, 1988;Pruchno et al, 1990;Whiteck, Hoyt, & Huck, 1994), and other times not (Cantor, 1983;Gilhooly, 1984;Jenkins, Parham, & Jenkins, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between disability and stress has at times been confirmed (Deimling & Bass, 1986;Schulz, Tompkins, Wood, & Decker, 1987;Stoller & Pugliesi, 1989), but more commonly not (George & Gwyther, 1986;Haley, Levine, Brown, & Bartolucci, 1987;Kinney & Stephens, 1989;Moritz, Kasl, & Berkman, 1989;Morris et al, 1988;Pagel et al, 1985). Similarly, a positive relationship between caregiver and care receiver has been seen as beneficial (Gilleard, Gilleard, Gledhill, & Whittick, 1984;Horowitz, 1985;Morris et al, 1988;Pruchno et al, 1990;Whiteck, Hoyt, & Huck, 1994), and other times not (Cantor, 1983;Gilhooly, 1984;Jenkins, Parham, & Jenkins, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…That Whites attend support groups more frequently than do minority group members is widely acknowledged. The effectiveness of participating in a support group as a mediator of caregiver stress is also well-documented (Barnes, Raskind, Scott, & Murphy, 1981;Gallagher, 1985;Jenkins, Parham, & Jenkins, 1985).…”
Section: Ethnic/cultural Issues In Caregiver Coping Patternsmentioning
confidence: 96%
“…Attempts to identify specific characteristics of caregiving detrimental to health and well-being have emphasized the quality and dynamics of the caregivercare recipient relationship (Niederehe & Scott, 1987), as well as the affective ties between the caregiver and carerecipient (Chenoweth & Spencer, 1986;Deimling & Bass, 1986;Fitting, Rabins, Lucas, & Eastham, 1986;Zarit, Todd, & Zarit, 1986). On the other hand, some studies have found that characteristics of the caregiver-care recipient relationship do not influence the caregiver's feelings about his or her role (Jenkins, Parham, & Jenkins, 1985;Zarit, Reever, & Bach-Peterson, 1980), leaving some to suggest more careful investigation of interpersonal factors (Birkel, 1987;DeLongis & O'Brien, 1990).…”
mentioning
confidence: 99%